CARRAGEENANS AS A MULTIFACETED BIOMATERIAL IN THE ERA OF BIOMEDICAL AND ENVIRONMENTAL INNOVATION - Zuñiga D, Martina; Montoya-Rodriguez, Diana; Rivas, Bernabe L (Journal of the Chilean Chemical Society, 2025)
Carrageenans are biomaterials of great interest due to their structural variability and physicochemical properties. This article provides a detailed review of the structural classification of carrageenans and its correlation with physical properties and specific applications, focusing on the various materials that can be obtained from them. Processing and modification methods are discussed to obtain gels, nanoparticles, films, and coatings, which possess unique properties that make them suitable for a wide range of applications. In the biomedical realm, carrageenans excel as scaffolds for tissue engineering, drug delivery systems, and wound healing materials, taking advantage of their biocompatibility and ability to form gels. In agriculture, they are used for the controlled release of fertilizers and pesticides, as well as biostimulants and soil improvers. In the food industry they act as thickening, stabilizing, and gelling agents in a wide range of products, from dairy to meat products, conferring texturising properties and improving stability. In addition, their role in environmental remediation is addressed, where in addition to their uses in agriculture to reduce the impact of different compounds, and water consumption, they are used for the removal of pollutants and water purification, thanks to their ability to form complexes with heavy metals and other pollutants. This review highlights the potential of carrageenans to inspire future innovations in the design of materials and technologies, underlining the importance of exploring and fully exploiting their potential and that of their derivatives to address current and future challenges in various sectors.